Diversifikasi Pendapatan, Kinerja Bank, dan Peran Moderasi Tipe Kepemilikan - Muharam, Harjum; Bellinda, Bianda (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2020)
Income diversification is one of the Bank's strategies to earn income. Non-Interest Income is the alternative to absorb income other than Net Interest Income. However, the level of Non-Interest Income of Commercial Banks in Indonesia is still at an average of 20%. Based on this problem, the study aimed to analyze the effect of Income Diversification, Non-Interest Income, and determination of Non-Interest Income which is Fee Commissions Income And Trading Income on the performance of Commercial Banks in Indonesia listed in the Bursa Efek Indonesia (BEI) period of 2014 – 2018. The condition of Commercial Bank’s stakeholders in Indonesia also changes because of raised number of mergers and acquisition that occur in Indonesian banks. Therefore, this study aimed to analyze the state-owned ownership and foreign ownership in moderating the effect of Income Diversification and Non-Interest Income on Commercial Banks’ performance in Indonesia listed in Bursa Efek Indonesia (BEI) period of 2014-2018. The results of this study indicate that Income Diversification, Non-Interest Income, and Fee Commissions Income have positive and significant effect on the Bank's performance. Banks with state-owned ownership has a negative and significant influence in moderating the effect of Income Diversification and Non-Interest Income on ROA. Meanwhile, Banks with foreign ownership has a positive and significant effect on the Bank’s performance.